Clinicopathological Spectrum and Outcome of Crescentic Glomerulonephritis: A Retrospective Study from North-East India (Journal of Renal and Hepatic Disorders, 2022)
Crescentic glomerulonephritis (CrGN) is characterized by the presence of crescents in more than 50% of glomeruli. This study aims to identify the etiology and clinicopathological features and outcomes of CrGN. In this observational study, 80 biopsy-proven CrGN were included. Patients’ demographic profile, clinical parameters, treatments, and outcomes were collected and analyzed. The mean age in our study population was 40.86 ± 16.5 years. Type II CrGN was the most common type of CrGN. Female predominance was observed in type I and type II CrGN. The highest percentage of glomeruli with crescents was seen in type I (87 ± 15.2%, P = 0.04), followed by type III and type II. At the last follow-up, mean estimated glomerular filtration rate was 25.8 ± 11.41 mL/min/1.73 m2 and was significantly lower in type I CrGN (11.6 ± 4.8 mL/min/1.73 m2 P = 0.001). The overall 5-year renal survival rate was 55% and was highest in type II (69.4%), followed by type III and type I (27.3%) CrGN (P = 0.0299). In our study, oliguria at the time of presentation, percentage of crescents, glomerular sclerosis, and moderate/severe IFTA were associated with poor renal outcomes. In conclusion, CrGN was seen in 5.7% of kidney biopsies in our study. Type II CrGN was the most common type of CrGN followed by type III CrGN. Renal survival was poor in type I CrGN patients compared to type II and type III CrGN. Also, oliguria, crescents, glomerular sclerosis, and moderate/severe IFTA were associated with poor renal outcomes.
Keywords: crescentic glomerulonephritis; pauci-immune glomerulonephritis; antineutrophil cytoplasmic antibodies–associated vasculitis; lupus nephritis; Ig A nephropathy